The lost diary of Sami Star - McCombie, Karen (Edinburgh: Barrington Stoke, 2018)
Life is hard for Hannah at the moment, At home, everyone's always arguing, and when she tries to talk to her friends, it feels like they're not really there for her. But everything changes when she comes across an abandoned diary in the park. It belongs to a girl called Sami Star, and fun-loving Sami sounds just the sort of friend that Hannah needs. Little does Hannah know that Sami needs her too..
Keywords: Children's stories